Investigation on Physical and Mechanical Properties of Abaca Fiber Composites Using Filament Winding. (2nd September 2022) - Alshgari, Razan A.; Hemalatha, N.; Suryavanshi, Ajay; Prasad, D. V. S. S. S. V.; Subalakshmi, R.; Abirami, M.; Amudha, M. J. R.; Wabaidur, Saikh Mohammad; Islam, M. Ataul; Christopher, David
Abstract : Composites that were made stronger with jute fiber and glass fiber were used to test the performance of filament wound abaca fiber composites. Tensile, bending, and dynamic mechanical analyses were used to figure out the mechanical properties of the composites. Fiber composites and glass-fiber composites were found to have higher density and mechanical properties than abaca fiber-based composites. This is because resin did not get into the cell cavity of the fiber's inner tissue structure. The abaca fiber composites that worked the worst were those in which the fibers were pulled out while the fibers on the surface were torn. The fiber-reinforced epoxy circumferential composite interface junction in the twisting abaca fiber circumferential composite was found to be more flexible and have a higher glass transition temperature than any of the other composites (6000 MPa). We found that twisting abaca fiber-naval ordnance laboratory and twisting abaca fiber-prepared circumferential composite had the lowest frequency dependence and performance variability. To improve composite properties, both the outside and inside structures of twisting abaca fiber need to be fixed. There is also a rise in fiber-to-resin contact and a rise in fiber surface area. The diameter of the fibers also gets smaller.